Assessment of vitamin status; A, E and D in Egyptian neonates with IUGR: a cross sectional study - Hanaa Reyad Abdallah; Abderahman A. Abdelrazek; Eman Refaat Youness; Hisham A. Orban; Marwa A. Mahmoud; Ahmed Helal El Sayed; Moushira Zaki (BMC Pediatrics, 2024)
Abstract Background Neonates with intrauterine growth retardation (IUGR) may present with fatal complications and permanent serious consequences. Vitamin status may influence fetal development. In this study we assessed vitamin A, E and D concentrations in umbilical cord blood in newborns with IUGR. Methods Maternal data were obtained. Neonatal assessment included; age of gestation calculated from last menstrual period, Ultrasound (U/S), new Ballard, Apgar scores and anthropometric measurements including; Head circumference, length and weight. WHO growth percentile curves were used. Vitamin A, E and D in cord blood samples were measured by high performance liquid chromatography (HPLC) and ELISA consecutively. Results A total of 86 full term newborns were enrolled in this study, 42 (48.8%) with IUGR with gestational age (33.59 ± 1.20) week by U/S and 44 (51.2%) appropriate for gestational age neonates with gestational age (38.70 ± 1.50). Ballard and Apgar scores (p < 0.05) and Z scores for weight, length and head circumference (p < 0.001) at birth were significantly lower in neonates with Intrauterine growth retardation (IUGR) than appropriate for gestational age (AGA) neonates. The levels of Vitamin A, E and D were significantly lower in the IUGR group than the AGA (p < 0.05) for all. Significant positive correlations of weight with vitamin A, and E cord blood levels were found (p < 0.05), while length was significantly positively correlated only with vitamin A (p < 0.05). Head circumference showed significant positive correlations with the three vitamins (p < 0.05) for all. Conclusion Neonates with IUGR had significantly lower levels of Vitamin A, E and D than AGA neonates. Significant positive correlations of weight with vitamin A, and E cord blood levels was detected, while neonatal length was associated only with vitamin A level. The present study highlights the significance of nutritional policies for inhibiting deficiency of these vitamins during pregnancy and childhood.